Studies on Nitrate-nitrogen Movement under Sub-surface Drip Irrigation in Potato - Tiwari, K N; Maji, M K; Biswas, U; Mal, P K (Journal of Agricultural Engineering, 2010)
Among various inputs, the modern agriculture is heavily dependent on the use of fertilizers and pesticides to meet the food requirements of ever-increasing population. Nitrate form of nitrogen is one of the major plant nutrients, and is mainly responsible for the pollution of soil and water resources. The movement of nitrate-nitrogen (NO3-N) in the soil is a complex, but largely affected by water movement. An attempt was made to study the dynamics of NO3-N under sub-surface drip irrigation in potato (Kufri-jyoti) crop. Four levels of fertilizer-N were applied at two depths of application with subsurface drip. The nitrogen fertigation levels were 40 %, 60 %, 80 % and 100 % of the recommended dose and replicated three times. Irrigation water requirement of the crop was estimated using cumulative pan evaporation data. The soil samples from three depths (0-15 cm, 15-30 cm and 30-45 cm) of the crop field were collected for chemical analysis. The maximum concentration of nitrate content was at 100 % fertigaton levels, followed by 80 % N level. The biometric observations showed that application of 100 % N fertigation through subsurface drip irrigation buried at 10 cm depth exhibited highest vegetative growth as compared to other N fertigation levels. The maximum yield of 23.84 t/ha was obtained under the same treatment, followed by 20.03 t/ha under the treatment 80 % N. The economic analysis indicated highest benefit-cost ratio of 2.11:1 for the treatment 100 % N (F4) followed by 1.64:1 for 80 % N.